Legislative functionalization in Fiqh Siyasah Perspective - Syamsuar (Cyber Media Indonesia, 2020)
The purpose of this study is to discuss about the function of legislation in Fiqh Siyasah point of view. According to Fiqh Siyasah,the legislative power is called al-sulthah al-tasyri’iyyah, which is tasked with forming a law that will be enforced in society for the benefit. The people who sit in the legislative institution should be selected people such as Mujtahid, Mufti,and the professional people in various fields. Further, there are some functions of legislative institution. Firstly, the provisions that are already contained in Al-quran and As-sunnah,the law issued by al-sulthah al-tasyri’iyyah is a ilahi law which is shariaed in Al-quran and As-sunnah. Secondly, making some creative reasonings or Ijtihad on the problems explicitly that are not elaborated in Al-quran and As-sunnah. Therefore, the sulthah al-tasyri’iyyah role is to carry out ijtihad to assign the law based on the knowledge of Mujtahid and Mufti. Abstrak Penelitian ini membahas tentang fungsi legislasi dalam pandangan fiqih siyasah. Adapun dalam Fikih Siyasah, kekuasaan legislatif disebut dengan al-sulthah al-tasyri’iyyah, yang bertugas untuk membentuk suatu hukum yang akan diberlakukan didalam masyarakat demi kemaslahatan. Orang-orang yang duduk dilembaga legislatif harus dari orang-orang pilihan seperti para mujtahid dan ahli fatwa (mufti) serta para pakar-pakar dalam berbagai bidang. Sedangkan fungsi dari lembaga legislatif adalah Pertama, ketentuan yang sudah terdapat dalam Al-Quran dan Sunnah, undang-undang yang dikeluarkan al-sulthah al-tasyri’iyyah adalah undang-undang yang bersifat ilahiah yang di syariatkan dalam Al-Quran dan Sunnah. Kedua, melakukan penalaran kreatif atau ijtihad terhadap permasalahan secara tegas yang tidak dijelaskan oleh Al-Quran dan Sunnah. Maka disinilah peran al-sulthah al-tasyri’iyyah yang di isi oleh para mujtahid atau ahli fatwa untuk melakukan ijtihad menetapkan hukumnya dengan ilmu yang mereka miliki.